Sole Expression: A Trauma-Informed Dance Intervention. Issue 5 (28th May 2019) - Lapum, Jennifer L.; Martin, Jennifer; Kennedy, Karyn; Turcotte, Catherine; Gregory, Heather
ABSTRACT: The primary treatment for individuals who have encountered violence and/or abuse is trauma-focused cognitive and behavioral modalities. However, these therapeutic approaches are not always effective for youth who have encountered this type of trauma. Trauma is often communicated through the body via physical ailments, particularly when words are insufficient to capture an individual's experience or when adequate processing of the trauma is not possible due to profound stress. Dance offers an alternative form of therapy that can address "where" the trauma is held, relieve tension, and restore a sense of ownership with one's body and mind. In this article, we discuss the development of Sole Expression, a trauma-informed hip-hop dance program for youth who have experienced abuse and/or exposure to violence. We provide an overview of establishing the team, securing funding, trauma training, program curriculum, and the related research. We conclude with recommendations for best practices that benefit both practitioners and the young people served.